Pengaruh Likuiditas, Leverage, Profitabilitas dan Capital Intensity Terhadap Agresivitas Pajak - Laksmi P, Kadek Wulandari; Ariwangsa, I G.N. Oka; Putri, Ni Putu Ayu Sriniken Dhamayanti; Putra P, Komang Widhya Sedana (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
Tax aggression is an action taken to ensure that income subject to tax is either calculated correctly or illegal tax avoidance, often known as tax fraud. The purpose of this study is to estimate the impact of liquidity, leverage, profitability, and capital intensity on tax aggression in food and beverage sub-sector manufacturing companies listed on the IDX throughout 2021-2022. Sampling was carried out by purposive sampling so that 26 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange were obtained that met several requirements. The results showed that liquidity and leverage have a negative effect on tax aggressiveness. Meanwhile, profitability and capital intensity have a positive and significant effect on tax aggressiveness